Printed, Soft, Nanostructured Strain Sensors for Monitoring of Structural Health and Human Physiology - Herbert, Robert; Lim, Hyo-Ryoung; Yeo, Woon-Hong (ACS applied materials & interfaces, 2020)
Soft strain sensors that are mechanically flexible or stretchable are of significant interest in the fields of structural health monitoring, human physiology, and human-machine interfaces. However, existing deformable strain sensors still suffer from complex fabrication processes, poor reusability, limited adhesion strength, or structural rigidity. In this work, we introduce a versatile, high-throughput fabrication method of nanostructured, soft material-enabled, miniaturized strain sensors for both structural health monitoring and human physiology detection. Aerosol jet printing of polyimide and silver nanowires enables multifunctional strain sensors with tunable resistance and gauge factor. Experimental study of soft material compositions and multilayered structures of the strain sensor demonstrates the capabilities of strong adhesion and conformal lamination on different surfaces without the use of conventional fixtures and/or tapes. A two-axis, printed strain gauge enables the detection of force-induced strain changes on a curved stem valve for structural health management while offering reusability over 10 times without losing the sensing performance. Direct comparison with a commercial film sensor captures the advantages of the printed soft sensor in enhanced gauge factor and sensitivity. Another type of a stretchable strain sensor in skin-wearable applications demonstrates a highly sensitive monitoring of a subject's motion, pulse, and breathing, validated by comparing it with a clinical-grade system. Overall, the presented comprehensive study of materials, mechanics, printing-based fabrication, and interfacial adhesion shows a great potential of the printed soft strain sensor for applications in continuous structural health monitoring, human health detection, machine-interfacing systems, and environmental condition monitoring.